Mediating role of profitability in the relationship between institutional ownership and firm value: Evidence from Indonesia - Giri Suseno; Endah Arianti Putri; Nurmala Sari; Willi Meilita; Jusniarty Sihite (Universitas Kristen Maranatha, 2026)
This study examines the effect of institutional ownership on profitability and firm value, with profitability as a mediating variable, in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, variable control is firm size and interest rate. The research sample includes 54 purposive-sampled manufacturing enterprises. Secondary data from IDX and company yearly financial statements is used. STATA version 17 is used for structural equation modelling (SEM) with bootstrapping data analysis. The study found that institutional ownership increases profitability (ROE) and firm value (PBV) at 5% and 10% significance levels, respectively. Profitability also increases company value at a 1% significance level. Profitability also mediates the effect of institutional ownership on firm value at the 10% significance level, indicating that institutional ownership can increase firm value through increased profitability. This study helps explain how institutional ownership boosts business value through profitability. This research has implications for regulators (OJK & IDX) and policymakers regarding corporate governance. Managers need to strengthen governance and transparency to maximize profitability and enhance company value. To better understand how institutional ownership affects business value, future research should expand variables, incorporate data from various industries, and conduct cross-country studies.